THE ASSOCIATION BETWEEN BODY MASS INDEX CATEGORY UNDERWEIGHT WITH PRIMARY DYSMENORRHEA PAIN LEVELS IN YOUNG WOMEN JUNIOR HIGH SCHOOL - Lasmi, Kadek Kristina Harum; Wibawa, Ari; Muliarta, I Made (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 3 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i03.p06, 2018)
ABSTRACT The Research aims to determine the association between body mass index underweight with primary dysmenorrhea pain level. Analytical research design cross sectional approach. Sample technique is systematic random sampling. The sample size is 52 female teenagers in SMP N 9 Denpasar and SMPK Santo Yoseph Denpasar. The technique of chi square test data analysis. The result of this research is the most mild pain level in normal body mass index which is 16 respondent (30,8%), moderate pain level in normal body mass index are 15 respondents (28,8%) and level of pain The most weight in the body mass index underweight category as many as 4 respondents (7.7%). From chi square test data analysis, p value is 0,041 so p <0,05. Result of statistic test hence can be concluded that there is significant relation between body mass index underweight with primary dysmenorrhea pain level. Keywords: primary dysmenorrhea, underweight